What a sucking louse can tell us: the use of the seal lice (Lepidophthirus macrorhini) from the southern elephant seal (Mirounga leonina) in isotopic analysis of hosts - Eder, Elena Beatriz; Leonardi, María Soledad (Polar Biology)
The southern elephant seal, Mirounga leonina, is one of the top predators inhabiting the Southern Ocean. Foraging at sea represents 80% of their annual cycle, during which they make extraordinary wide-ranging trips with long, deep, and continuous dives. Their feeding habits have been broadly studied using both traditional and advanced techniques, like stable isotope analysis. Here, we analyzed stable isotope ratios of C and N of host and sucking lice tissues to investigate the potential use of lice to infer the isotopic patterns of their host at a major scale while using a less invasive method. We collected samples of blood and lice, Lepidophthirus macrorhini, from 15 weaned pups in Península Valdés (Chubut, Argentina). C and N isotopic signals of lice and pups were correlated. The δ13C values of the lice were not different from those of their hosts, while the δ15N signals were statistically significantly enriched with respect to those of the pups. The isotopic composition of the lice would predictably mirror that of their hosts. However, the values of Δ13C and Δ15N (difference between lice and pup signals) differed from the literature-based reference values for hematophagous ectoparasites, indicating that lice could have changed the host recently or that the residence time in the pups has not been enough. Given that mothers and weaned pups differ isotopically due to lactation, the isotopic composition of lice could therefore be more representative of signals from females, implying a useful and a safe tool for identifying and measuring the magnitude of trophic interactions in this species. Fil: Eder, Elena Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina ...